2020
DOI: 10.1097/pts.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Count Technology on Retained Surgical Items Rates in the Veterans Health Administration

Abstract: Objectives The aim of the study was to compare retained surgical item (RSI) rates for 137 Veterans Health Administration Surgery Programs with and without surgical count technology and the root cause analysis (RCA) for soft good RSI events between October 1, 2009 and December 31, 2016. A 2017 survey identified 46 programs to have independently acquired surgical count technology. Methods Retained surgical item rates were calculated by the sum of events (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…16 As such, the fact that these procedures were not sufficient to avoid the retention of surgical items is a relevant consideration for contemporary prevention and protective strategies. Our findings in this context align with the recent findings by Gunnar et al 54 in their study of root cause analysis of RSI events, which found that a majority of incidents (64%) involved human factors issues (eg, staffing changes during shifts, staff fatigue), policy/procedure failures (eg, failure to perform methodical wound sweep) or communication errors. 54 In addition, standard and usual processes outlined in ACORN Standards for locating missing items in the event of a discrepancy in the count, including immediately notifying the surgeon, requesting a thorough re-exploration of the wound, search of environmental surroundings and intra-operative imaging, do not provide a completely effective prevention strategy.…”
Section: Need For Multidisciplinary Guidelines For Perioperative Practicesupporting
confidence: 91%
See 2 more Smart Citations
“…16 As such, the fact that these procedures were not sufficient to avoid the retention of surgical items is a relevant consideration for contemporary prevention and protective strategies. Our findings in this context align with the recent findings by Gunnar et al 54 in their study of root cause analysis of RSI events, which found that a majority of incidents (64%) involved human factors issues (eg, staffing changes during shifts, staff fatigue), policy/procedure failures (eg, failure to perform methodical wound sweep) or communication errors. 54 In addition, standard and usual processes outlined in ACORN Standards for locating missing items in the event of a discrepancy in the count, including immediately notifying the surgeon, requesting a thorough re-exploration of the wound, search of environmental surroundings and intra-operative imaging, do not provide a completely effective prevention strategy.…”
Section: Need For Multidisciplinary Guidelines For Perioperative Practicesupporting
confidence: 91%
“…Our findings in this context align with the recent findings by Gunnar et al 54 in their study of root cause analysis of RSI events, which found that a majority of incidents (64%) involved human factors issues (eg, staffing changes during shifts, staff fatigue), policy/procedure failures (eg, failure to perform methodical wound sweep) or communication errors. 54 In addition, standard and usual processes outlined in ACORN Standards for locating missing items in the event of a discrepancy in the count, including immediately notifying the surgeon, requesting a thorough re-exploration of the wound, search of environmental surroundings and intra-operative imaging, do not provide a completely effective prevention strategy. This conclusion, derived from an analysis of case law, is supported not only by the literature but also by state government patient safety reports that point to procedural non-compliance as a key contributing factor to surgical item retention.…”
Section: Need For Multidisciplinary Guidelines For Perioperative Practicesupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with a similar review from Portugal of more than 700,000 hemodialysis treatments reporting a serious bleeding event rate of 3.4 incidents per 100,000 treatments 14 . For event comparison, this rate for VHA hemodialysis bleeding events is similar to published rates for VHA wrong site surgery and retained surgical item events 15,16 …”
Section: Discussionsupporting
confidence: 74%
“…However, sometimes the answer to a patient safety concern does not lie in a piece of equipment or technology. In a review of inaccurate surgical counts and RSIs, investigators determined that human behavior can be involved in the root cause of some adverse events 8 . Generally, perioperative personnel complete the surgical count to identify the location of surgical items during specific moments of a procedure (eg, before making or closing the incision) 9 .…”
Section: Causes Of Rsismentioning
confidence: 99%